5-Lipoxygenase Pathway, Dendritic Cells, and Adaptive Immunity. Issue 2 (30th June 2004) - Hedi, Harizi; Norbert, Gualde
Abstract : 5-lipoxygenase (5-LO) pathway is the major source of potent proinflammatory leukotrienes (LTs) issued from the metabolism of arachidonic acid (AA), and best known for their roles in the pathogenesis of asthma. These lipid mediators are mainly released from myeloid cells and may act as physiological autocrine and paracrine signalling molecules, and play a central role in regulating the interaction between innate and adaptive immunity. The biological actions of LTs including their immunoregulatory and proinflammatory effects are mediated through extracellular specific G-protein-coupled receptors. Despite their role in inflammatory cells, such as neutrophils and macrophages, LTs may have important effects on dendritic cells (DC)-mediated adaptive immunity. Several lines of evidence show that DC not only are important source of LTs, but also become targets of their actions by producing other lipid mediators and proinflammatory molecules. This review focuses on advances in 5-LO pathway biology, the production of LTs from DC and their role on various cells of immune system and in adaptive immunity.